2021
DOI: 10.1007/s00134-021-06401-6
|View full text |Cite
|
Sign up to set email alerts
|

Restrictive fluid management versus usual care in acute kidney injury (REVERSE-AKI): a pilot randomized controlled feasibility trial

Abstract: Purpose: We compared a restrictive fluid management strategy to usual care among critically ill patients with acute kidney injury (AKI) who had received initial fluid resuscitation.Methods: This multicenter feasibility trial randomized 100 AKI patients 1:1 in seven ICUs in Europe and Australia. Restrictive fluid management included targeting negative or neutral daily fluid balance by minimizing fluid input and/or enhancing urine output with diuretics administered at the discretion of the clinician. Fluid bolus… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2
1

Citation Types

1
35
0
2

Year Published

2021
2021
2024
2024

Publication Types

Select...
7
2

Relationship

1
8

Authors

Journals

citations
Cited by 48 publications
(41 citation statements)
references
References 36 publications
(68 reference statements)
1
35
0
2
Order By: Relevance
“…Those progression criteria were another critical decision in pilot sample size calculation. Thresholds were chosen after examining other pilot feasibility studies of complex interventions (defined as interventions with several interacting components) and summarized in Additional file 1 : Table S2 [ 25 27 ].…”
Section: Methodsmentioning
confidence: 99%
See 1 more Smart Citation
“…Those progression criteria were another critical decision in pilot sample size calculation. Thresholds were chosen after examining other pilot feasibility studies of complex interventions (defined as interventions with several interacting components) and summarized in Additional file 1 : Table S2 [ 25 27 ].…”
Section: Methodsmentioning
confidence: 99%
“…Sensitivity analysis for sedative and vasopressor requirements, excluding patients started on NMB post-randomization, was conducted. We also performed an additional post hoc sensitivity analysis in per-protocol population, defined as mITT population after exclusion of subjects who did not complete 48 h post-randomization [ 27 ]. We ensured immediate data entry and identified missing data quickly, and issues were resolved promptly.…”
Section: Methodsmentioning
confidence: 99%
“…However, the enrollment of both septic and non-septic should reflect the nature of this real-world study. Moreover, the relative neutral fluid balance among patients enrolled during 2015-2019 aligns with a shift toward more restrictive fluid management in critically ill patients reported in recent trials (27).…”
Section: Discussionmentioning
confidence: 62%
“…The mortality rate in the intervention group is similar to that in other recent sepsis trials [31,32], while that in the standard care group is unexpectedly low. Furthermore, other recent trials in critically ill patients have suggested comparable or better outcomes resulting from restrictive fluid strategies [11,25,33]. The likelihood that this finding represents a type 1 error is, therefore, high.…”
Section: Discussionmentioning
confidence: 94%